Contexts for reading the reader: why the private library of a twentieth-century Canadian woman is important - Edwards, Mary Jane (Studia Anglica Posnaniensia, 2025)
An article on a library collected in the twentieth century by a Canadian woman may seem of little relevance to a topic called “A way with words”. Still, one of the many contexts in which we read books is their existence as objects in various kinds of libraries. This article’s subject is a library of over seventeen hundred books accumulated in the twentieth century in a modest house on a modest street in the mid-sized city of Brantford, Ontario, by a woman who had graduated from high school, but who would now be considered to have had a modest education. As well as gathering these books, she read them. In most she signed her name; in many she recorded such information as the date of their acquisition; and, although she did not usually mark them up, she sometimes left objects in them. Over the years she also listed them in notebooks. When she died, her nephew boxed the books in no particular order. Since then, they have been moved several times, and more than half have disappeared. Over six hundred of the books, however, have survived and are now deposited in the MacOdrum Library at Carleton University, Ottawa. While I had these books in my house, I prepared lists of them in alphabetical order according to author, and I arranged them alphabetically in bankers’ boxes. As I reorganised this library, I was impressed with what it revealed about not only Bibliography and Textual Studies, including the History of the Book, particularly as these subjects concern Canada, but also about such topics as Canadian culture and the influence of books and reading on the shaping of images of women in the twentieth century. My article demonstrates the importance of this private library’s “way with words”.